Dietary Recommendations for the Prevention of Type 2 diabetes: What Are They Based on? - Patrice Carter; Kamlesh Khunti; Melanie J. Davies (Journal of Nutrition and Metabolism)
Introduction. Type 2 diabetes is increasing in all populations and all age groups across the world. Areas undergoing rapid westernisation and rapid nutrition transition are seeing the greatest increases in prevalence suggesting that environmental factors are important. Studies from around the world have shown that dietary modification for the prevention of T2DM can be successful; however which dietary factors are important remains to be fully elucidated. The WHO, ADA, and Diabetes UK have developed guidelines for the prevention of T2DM even though the WHO states that data from lifestyle modification programmes does not allow for the disentanglement of dietary factors. Aim of Review. The aim of this focused review is to evaluate the current dietary recommendations for the prevention of T2DM. In addition we aim to explore the available evidence from both observation studies and clinical trials to determine whether these recommendations are appropriate.